Plant interactions control the carbon distribution of Dodonaea viscosa in karst regions. - Genzhu Wang; Guoyong Tang; Danbo Pang; Yuguo Liu; Long Wan; Jinxing Zhou (PLoS ONE)
Biomass and carbon (C) distribution are suggested as strategies of plant responses to resource stress. Understanding the distribution patterns of biomass and C is the key to vegetation restoration in fragile ecosystems, however, there is limited understanding of the intraspecific biomass and C distributions of shrubs resulting from plant interactions in karst areas. In this study, three vegetation restoration types, a Dodonaea viscosa monoculture (DM), a Eucalyptus maideni and D. viscosa mixed-species plantation (EDP) and a Pinus massoniana and D. viscosa mixed-species plantation (PDP), were selected to determine the effects of plant interactions on the variations in the C distributions of D. viscosa among the three vegetation restoration types following 7 years of restoration. The results showed that: (1) plant interactions decreased the leaf biomass fraction. The interaction of P. massoniana and D. viscosa decreased the branch biomass fraction and increased the stem and root biomass fraction, but not the interaction of E. maideni and D. viscosa. Plant interactions changed the C concentrations of stems and roots rather than those of leaves and branches. (2) Plant interactions affected the soil nutrients and forest characteristics significantly. Meanwhile, the biomass distribution was affected by soil total nitrogen, clumping index and gap fraction; the C concentrations were influenced by the leaf area index and soil total phosphorus. (3) The C storage proportions of all the components correlated significantly with the proportion of biomass. Our results suggested that both the biomass distribution and C concentration of D. viscosa were affected by plant interactions, however, the biomass fraction not the C concentration determines the C storage fraction characteristics for D. viscosa.